Between development and destruction An enquiry into the causes of conflict in post-colonial states - Goor, Luc van de.; Rupesinghe, Kumar; Sciarone, Paul. (Houndmills, Basingstoke, Hampshire : Macmillan Press ; New York : St. Martin's Press, 1996)
Much has already been written about the effects of the changes of the Cold War on conflict. The ongoing disengagement of East and West from bipolar Cold-War politics has resulted in an unstable international political situation which is characterized by regional conflicts.
"The Netherlands Ministry of Foreign Affairs (DGIS) in association with the Netherlands Institute of International Relations, CLINGENDAEL, The Hague".
Keywords: Civil war; Regionalism (International organization); Security, International; International economic relations